METHODOLOGY OF SYSTEMIC RISK MANAGEMENT ADJUSTED FOR THE RUSSIAN CREDIT MARKET ENVIRONMENT - J. I. Petrova; V. E. Rasskazov; V. N. Salin; V. T. Sevruk (Финансы: теория и практика)
The current study is devoted to the methodology of systemic risk management adjusted for the Russian credit market. Among specific sources of systemic the following risks were emphasized: access of a banking sector to market liquidity and currency fluctuations in the short term; financial contagion, economic bubbles and sovereign default risk in the long term. The Hui-Heubel ratio was applied to assess depth and volume of market liquidity. It was proved that there is a temporary market liquidity surplus. Currency risk was tested with application of VaR, historical simulation method, which supported observed tendency to economic stabilization. In both cases conditional and unconditional volatility were determined with GARCH method. Moreover, a methodology of stress-testing described in the paper presents a convenient solution to investigate effects of uncommon risks, such as financial contagion, economic bubbles and sovereign default risk. The current study could be applied to create personalized strategy of systemic risk prevention for banks or any commercial organization dealing with an unpredictable Russian financial market.